A distinct source and differentiation history for Kolumbo submarine volcano, Santorini volcanic field, Aegean arc. (16th August 2016) - Klaver, Martijn; Carey, Steven; Nomikou, Paraskevi; Smet, Ingrid; Godelitsas, Athanasios; Vroon, Pieter
Abstract: This study reports the first detailed geochemical characterization of Kolumbo submarine volcano in order to investigate the role of source heterogeneity in controlling geochemical variability within the Santorini volcanic field in the central Aegean arc. Kolumbo, situated 15 km to the northeast of Santorini, last erupted in 1650 AD and is thus closely associated with the Santorini volcanic system in space and time. Samples taken by remotely‐operated vehicle that were analyzed for major element, trace element and Sr‐Nd‐Hf‐Pb isotope composition include the 1650 AD and underlying K2 rhyolitic, enclave‐bearing pumices that are nearly identical in composition (73 wt.% SiO2, 4.2 wt.% K2 O). Lava bodies exposed in the crater and enclaves are basalts to andesites (52–60 wt.% SiO2 ). Biotite and amphibole are common phenocryst phases, in contrast with the typically anhydrous mineral assemblages of Santorini. The strong geochemical signature of amphibole fractionation and the assimilation of lower crustal basement in the petrogenesis of the Kolumbo magmas indicates that Kolumbo and Santorini underwent different crustal differentiation histories and that their crustal magmatic systems are unrelated. Moreover, the Kolumbo samples are derived from a distinct, more enriched mantle source that is characterized by high Nb/Yb (>3) and low 206 Pb/ 204 Pb (<18.82) that has not been recognized in the Santorini volcanic products. The strong dissimilarity in both petrogenesis and inferred mantle sources between Kolumbo and Santorini suggests that pronounced source variations can be manifested in arc magmas that are closely associated in space and time within a single volcanic field. Key Points: A trace element and Sr‐Nd‐Hf‐Pb isotope study of Kolumbo submarine volcano within the Santorini volcanic field The magmatic systems of Kolumbo and Santorini are unrelated and Kolumbo taps a distinct enriched mantle source Mantle source variations can be manifested in temporally associated arc magmas within the same volcanic field